Investigation of chloride‐induced pitting corrosion of steel in concrete with innovative methods. Issue 6 (25th April 2016) - Ebell, G.; Burkert, A.; Fischer, J.; Lehmann, J.; Müller, T.; Meinel, D.; Paetsch, O.
Abstract : The combination of electrochemical and 3D computed tomography (CT) investigations offers the possibility of verifying electrochemical measurements non‐destructively. Determining the steel surfaces damaged by pitting corrosion allows developing specimens having damage pattern corresponding to practice. Corrosion phenomena like decoupled pitting corrosion cannot be verified by electrochemical measurements only, but with the combination of those two kinds of investigations it is possible. Another advantage is the minimization of the number of samples. The classical experimental procedure requires the destruction of samples after each damage step. This can be avoided by the use of 3D computed tomography. As long as the corrosion phenomena are completely within the examination zone shown by the 3D computed tomography, the electrochemical measurements can be calculated on an area basis to get the specific corrosion rate or polarization resistance. Abstract : The combination of electrochemical and 3D computed tomography (CT) investigations offers the possibility of verifying electrochemical measurements non‐destructively. Determining the steel surfaces damaged by pitting corrosion allows developing specimens having damage pattern corresponding to practice.